2020
DOI: 10.3390/vaccines8020241
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Filovirus Vaccine Candidate: Co-Expression of Ebola, Sudan, and Marburg Antigens in a Single Vector

Abstract: In the infectious diseases field, protective immunity against individual virus species or strains does not always confer cross-reactive immunity to closely related viruses, leaving individuals susceptible to disease after exposure to related virus species. This is a significant hurdle in the field of vaccine development, in which broadly protective vaccines represent an unmet need. This is particularly evident for filoviruses, as there are multiple family members that can cause lethal haemorrhagic fever, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Figure 1 ). A ChAdOx1 vaccine encoding an irrelevant filovirus antigen (EBOV) was used as a negative control, 20 which showed a low level of binding to the anti-ChAdOx1 nCoV-19 vaccine serum (∼0.5–2% cells across all experiments). This observation accounts for antibodies raised against the vector itself rather that the vaccine antigen.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 ). A ChAdOx1 vaccine encoding an irrelevant filovirus antigen (EBOV) was used as a negative control, 20 which showed a low level of binding to the anti-ChAdOx1 nCoV-19 vaccine serum (∼0.5–2% cells across all experiments). This observation accounts for antibodies raised against the vector itself rather that the vaccine antigen.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). A ChAdOx1 vaccine encoding an irrelevant filovirus antigen (EBOV) was used as a negative control ( 20 ), which showed a low level of binding to the anti-ChAdOx1 nCoV-19 vaccine serum (~0.5–2% cells across all experiments). This observation accounts for antibodies raised against the vector itself rather that the vaccine antigen.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-clinical work which is expected to lead into clinical trials in the near future include ChAdOx1 vectored vaccines expressing Ebola (Bivalent), Crimean-Congo Hemorrhagic Fever, Nipah and Lassa antigens. See 4.11 [22] , [24] , [25] 5.2. What is the identity and source of the transgene?…”
Section: Introductionmentioning
confidence: 99%
“…Several pre-clinical studies have been performed using the ChAdOx1 vector including preliminary research of vaccine candidates for use in potential pandemic situations. Studies in small animal models have shown good potential of a number of ChAdOx1 vectored vaccines including those encoding antigens from influenza virus [19] , [20] , [21] , Nipah virus [22] , Zika virus [23] , Lassa virus [24] , filoviruses [25] , MERS-Cov virus [26] , SARS-CoV-2 virus [27] , [28] , [29] , blue tongue virus [30] , Rift Valley fever virus [31] , [32] , [33] , Chikungunya virus [34] , [35] , Human Immunodeficiency virus (HIV) [36] , [37] , Human papilloma virus (HPV) [38] , Hepatitis C virus [39] , [40] and Hepatitis B virus [41] . In some studies, large animals specific for the viral disease of concern were used, for example, pigs for ChAdOx1 expressing influenza virus haemagglutinin, sheep for the ChAdOx1 vector expressing blue tongue virus antigens, and sheep, cattle, dromedary camels and goats for ChAdOx1 expressing Rift Valley fever virus antigens.…”
Section: Introductionmentioning
confidence: 99%